1996
DOI: 10.1074/jbc.271.30.17927
|View full text |Cite
|
Sign up to set email alerts
|

COOH-terminal Extended Recombinant Amphiregulin with Bioactivity Comparable with Naturally Derived Growth Factor

Abstract: The mature secreted form of the epidermal growth factor (EGF) receptor ligand amphiregulin (AR) is reported to be an 84-amino acid residue polypeptide, which is generated by proteolytic processing of a 252-amino acid precursor. This form of recombinant AR (rAR84) and two forms with COOH-terminal extensions corresponding to sequences from the AR precursor (rAR87 and rAR92) were expressed at high levels in Escherichia coli, oxidized to the correct disulfide arrangement, and purified to homogeneity. rAR84 compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Anti-EGFR antibodies and EGFR antisense RNA expression inhibited the transformed phenotype of NS2T2A1 cells (Ma et al, 1998), as was shown previously in other breast cancer cell lines or human tumors in vivo (review see Modjtahedi and Dean, 1994). AR is secreted as a monomer of either 81 or 87 amino acid residues after proteolytic cleavage of the 252 amino acid transmembrane precursor (Plowman et al, 1990;Shoyab et al, 1989;Thompson et al, 1996), with a molecular weight ranging from 9.5 ± 60 kD, depending on the degree of glycosylation and NH2-terminal processing (Brown et al, 1998;Martinez-Lacaci et al, 1995Johnson et al, 1993b;Shoyab et al, 1988). In our NS2T2A1 cells, only the 55 ± 60 kD form of the AR was detected by Western blot analysis in the total protein lysate with the AR 605 polyclonal antibody.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Anti-EGFR antibodies and EGFR antisense RNA expression inhibited the transformed phenotype of NS2T2A1 cells (Ma et al, 1998), as was shown previously in other breast cancer cell lines or human tumors in vivo (review see Modjtahedi and Dean, 1994). AR is secreted as a monomer of either 81 or 87 amino acid residues after proteolytic cleavage of the 252 amino acid transmembrane precursor (Plowman et al, 1990;Shoyab et al, 1989;Thompson et al, 1996), with a molecular weight ranging from 9.5 ± 60 kD, depending on the degree of glycosylation and NH2-terminal processing (Brown et al, 1998;Martinez-Lacaci et al, 1995Johnson et al, 1993b;Shoyab et al, 1988). In our NS2T2A1 cells, only the 55 ± 60 kD form of the AR was detected by Western blot analysis in the total protein lysate with the AR 605 polyclonal antibody.…”
Section: Discussionsupporting
confidence: 61%
“…In most instances AR functions as a mitogen, but can inhibit the growth of human cancer cells, depending upon the concentration used, the presence of other growth factors, and the nature of the cell lines (Cook et al, 1991;Johnson et al, 1991Johnson et al, , 1992Johnson et al, , 1993aJohnson et al, , 1994Plowman et al, 1990;Shoyab et al, 1988;Thompson et al, 1996). In vitro, antisense oligonucleotides against AR were reported to partially inhibit AR expression and anchorage-dependent growth of immortalized-nontransformed human mammary epithelial 184A1N4 cells (Kenney et al, 1993) and human pancreatic cancer T3M4 cells (Funatomi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EGF and betacellulin worked well at 10 ng/ml, whereas amphiregulin was not effective at 10 ng/ml, but was effective at 1000 ng/ml. This difference in the effective concentration may be due to the difference in binding affinity, since the affinity of amphiregulin is several orders of magnitude less than that of EGF [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EGF and betacellulin worked well at 10 ng/ml, whereas amphiregulin was not effective at 10 ng/ml, but was effective at 1000 ng/ml. This difference in the effective concentration may be due to the difference in binding affinity, since the affinity of amphiregulin is several orders of magnitude less than that of EGF [26,27].Furthermore, it is very interesting that a combination of EGF with another EGF-family member (amphiregulin or betacellulin), as compared with EGF alone, improved the percentage of oocytes developing to the metaphase-II stage. A similar synergistic effect on oocyte maturation has been observed in buffalo COCs exposed to EGF plus IGF-I [28].…”
mentioning
confidence: 99%
“…GRB2-glutathione S-transferase (GST) fusion protein were obtained from Santa Cruz Biotechnology (Santa Cruz, CA). The 87-amino acid residue form of recombinant human AR was generated as described previously (12). Recombinant human EGF was obtained from PeproTech, Inc. (Rocky Hill, NJ).…”
Section: Methodsmentioning
confidence: 99%